An overview of mechanization in chhana production - V K, Ammu; Minz, P S; Singh, A K; Vairat, A D; Juneja, Amit Kumar; Jayswal, Dharin Kumar (Indian Journal of Dairy Science, 2020)
Chhana, regarded as the Indian counter part of soft cottage cheese is a heat acid coagulated milk product that serves as the base for a variety of milk products such as rasogolla, sandesh, paneer, cham cham, chhana podo, chhana kheer, kheermohan etc. Process mechanization of chhana and chhana based sweets is of huge scope due to the growing momentum in consumer demand for Traditional Indian milk products. Strengthening the knowledge base available for the technology of production of chhana is required to upgrade the existing systems with process automation and control. The main objective of all new technological interventions and improved mechanization systems for chhana developed so far is on yielding chhana of defined moisture content, soft texture and uniform quality along with reducing the cost and production time. Development of an improved mechanized systems for the rapid and hygienic production of chhana at small scale level is an urgent need of the hour. Mechanizations in various stages of chhana production can be integrated to the continuous system of chhana production. This article highlights the technological interventions and mechanization in the manufacture of chhana. In addition, the effect of coagulants in the manufacture of chhana, nutritive value and textural attributes of chhana are also discussed.